Kompetensi Aparatur Desa, Komitmen Organisasi, Partisipasi Masyarakat Dan Penerapan Sistem Teknologi Informasi Terhadap Akuntabilitas Pemerintah Desa Dalam Mengelola Alokasi Dana Desa - Wakhidian Solehatur Rohmah; Ardyan Firdausi Mustoffa; Nurul Hidayah (Faculty of Economics and Business, Universitas Stikubank, 2022)
This research has an impact on the ability of village officials, organizational commitment, community participation, and the use of information technology systems on village government accountability in managing village village funds in all Genangan sub-districts. This survey uses primary data from questionnaires distributed to 15 villages in the Genangoan District, Ponologo Regency. For data analysis, we used multiple regression analysis. Based on the results of the first hypothesis study, there is a positive influence between the capacity of village officials and the accountability of village resource allocation management. The results of testing the second hypothesis have a positive effect on organizational involvement and accountability of village fund allocation. The results of the third research hypothesis indicate that community participation has a positive effect on accountability in the management of village funds. The results of the fourth research hypothesis indicate that there is a positive effect of using IMS on accountability in the management of ADD. Meanwhile, the results of simultaneous hypothesis testing show that the capacity of village officials, organizational commitment, community participation, and the application of information technology systems together affect the accountability of resource allocation management Village.”